Polysemy and context: teachers' classroom language for understanding physical science - White, Regina (My University, 2016)
A debate in South Africa on learner performance in Physical Science inevitably leads to the issue of proficiency in the language of learning and teaching (LoLT). The researcher is of the opinion that general understanding of the meaning of proficiency in LoLT usually refers to the ability to read and write well in that language which happens to be English in the majority of South African high schools. As low as 7% of the South African school going population regard themselves as English speaking (Department of Basic Education, 2010). The status of English as lingua franca has caused parents and teachers to believe that it is in the interest of learners to be taught in English (Wildsmith-Cromarty & Gordon, 2009). This view resulted that the debate on proficiency includes amongst others, opinions of those who propagate home language teaching and those who call for English as the preferred medium of instruction. This research contributes to the debate on proficiency by pointing to the important contribution that the science teacher can make to enculturate learners into the language of school science. The fact that both English First Additional Language learners (EFALs) as well as English Home Language learners (EHLs) struggle to understand Physical Science (Probyn, 2015) is indicative of the important role that the science teacher can play in assisting learners to understand Physical Science. In lieu of this, teachers are encouraged to focus on vocabulary building as well as the manner in which LoLT is employed to construe science knowledge. This is a functional view of language, namely, that language is used to convey a particular meaning hence the language differs across registers. Michael Halliday (1993) is credited for the development of a systemic functional linguistic view on language. This study analysed two teachers’ classroom languages from a Systemic Functional Linguistic (SFL) perspective with specific emphasis on the register variables field and mode. Results show that LoLT was perceived as transparent when learners are EHLs and considered a barrier to learning Physical Science if learners are EFALs. In both cases, teachers seemed unable to enculturate learners into the language of school science when used to convey science meaning. An absence of that focus is what Bernstein called an “invisible pedagogy
A research report submitted to the Faculty of Science, in partial fulfilment of the requirements for the degree of Master of Science in Science Education, University of the Witwatersrand. November 5, 2016.
Keywords: Physical sciences; Physics--Study and teaching (Secondary)--South Africa; Language and languages--Usage